Analysis of the Mythical Discourse of “La esfinge de oro” by Carlos Raúl Sepúlveda - Mehmet İlgürel (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
In this work we study “La esfinge de oro” (1988) by Carlos Raúl Sepúlveda, an important figure in Chilean fantastic and science fiction literature. Firstly, we carry out an analysis of the story from Gilbert Durand’s perspective of the imaginary based on the schemes, archetypes, and symbols that the story presents. In terms of symbolic imagination, the story is characterized by a polarization of images that is reflected more clearly and intensely in two crucial spaces for the protagonist, Ñuble: his hometown, and the Chilean capital. The first of these two coincides with the isotopy of images that the French thinker calls the Nocturnal Regime of the imaginary. And from this point of view, urban images, among others, that are reflected in a negative way, are associated with the Diurnal Regime. In the study of images and concepts, we also assume the complementary perspectives of other authors such as Mircea Eliade and Northrop Frye. This study in general provides the basis for the analysis of the synchronic and diachronic relationships of the story. Through the redundant mythemes determined in the present analysis, we arrive at the heroic myth inherent in the short story, which is revealed through Lévi Strauss’s method, as used in Durand’s myth criticism.